Screening for cognitive symptoms among cancer patients during chemotherapy: Sensitivity and specificity of a single item self‐report cognitive change score. Issue 8 (30th March 2022) - Fardell, Joanna E.; Bray, Victoria; Bell, Melanie L.; Rabe, Brooke; Dhillon, Haryana; Vardy, Janette L.
Abstract: Objectives: Cognitive symptoms are commonly reported among cancer patients and survivors, yet guidance on when self‐reported cognitive symptoms warrant follow‐up is lacking. We sought to establish cut‐off scores for identifying patients with perceived low cognitive functioning on widely used self‐report measures of cognition and a novel single item Cognitive Change Score. Methods: Adult patients diagnosed with invasive cancer who had completed at least one cycle of chemotherapy completed a questionnaire containing the EORTC‐Cognitive Function (CF) subscale, Functional Assessment of Cancer Therapy‐Cognitive Function (FACT‐COG) Perceived Cognitive Impairment (PCI) and our Cognitive Change Score (CCS). We used receiver operating characteristic analyses to establish the discriminative ability of these measures against the Patient's Assessment of Own Functioning Inventory (PAOFI) as our reference standard. We chose cut‐off scores on each measure that maximised both sensitivity and specificity for identifying patients with self‐reported low CF. Results: We recruited 294 participants (55.8% women, mean age 56.6 years) with mixed cancer diagnoses (25.5 months since diagnosis). On the CCS, 77.6% reported some cognitive change since starting chemotherapy. On the PAOFI 36% had low CF. The following cut‐off scores identified cases of low CF: ≥28.5 on the CCS (75.5% sensitivity, 67.6% specificity); ≤75.0 on the European Organisation for Research and Treatment of Cancer, QLQ‐C30 Cognitive Functioning scale (90.9% sensitivity, 57.1% specificity); ≤55.1 on the FACT‐COG PCI‐18 (84.8% sensitivity, 76.2% specificity), and ≤59.5 on the FACT‐COG PCI‐20 (78.8% sensitivity, 84.1% specificity). Conclusions: We found a single item question asking about cognitive change has acceptable discrimination between patients with self‐reported normal and low CF when compared to other more comprehensive self‐report measures of cognitive symptoms. Further validation work is required.